Digital Telehealth Innovations in Pediatric Palliative Care During the COVID-19 Pandemic: A Systematic Review: Inovasi Digital Telehealth Pada Perawatan Paliatif Anak Selama Pandemi COVID-19: A Systematic Review - Fernanda, Pradita Ayu; Mintarsih, Sri; Fitria, Cemy Nur (Prosiding University Research Colloquium, 2023)
Introduction: Pediatric subspecialty care, including multidisciplinary palliative care, tends to be located in urban academic centers or children's hospitals. Telehealth provides an opportunity to care for patients who would otherwise not be able to access services. We present a case in which telehealth was used to provide counseling services to a patient who was unable to receive services. The purpose of writing this review article is to determine the effectiveness of telehealth innovations used for children with palliative care during the COVID-19 pandemic. Methods: This systematic review results from searches from five electronic databases (Scopus, ProQuest, Web of Science, Science Direct, PubMed and Sage). The criteria for articles in this research are articles published in 2017 – 2022, full text, articles in English or Indonesian, and research methods using case study, descriptive, qualitative, cross sectional studies. The keywords used are ("teleheatlh" OR "telemedicine") AND ("children" OR "child") AND ("COVID-19" OR "COVID-19 Pandemic") AND ("palliative" OR "palliative care") . The review used the Joanna Briggs Institute Guidelines for quality reviews and the Prisma checklist to guide these reviews. Results : We found fifteen studies that met the inclusion criteria in the review. The included studies contain digital telehealth innovations in pediatric palliative care during the COVID-19 pandemic. Respondents in several studies were pediatric patients aged 7-18 years who were undergoing palliative care. Telehealth using the video conferencing method is effectively used in palliative care for pediatric patients during the COVID-19 pandemic. Conclusion: All studies reveal that telehalth is effective during the COVID-19 pandemic.